Adaptasi dan Dukungan Keluarga dengan Resiliensi Pekerja - Lestari, Sofiyah Nia; Amanda Pasca Rini; Eko April Ariyanto (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2025)
The importance of economic factors in a family encourages individuals to work hard to do everything necessary to fulfill some of their needs, one of which is to remain resilient to earn a living in the midst of bad air pollution in the capital city. This study aims to determine the relationship between adaptation and family support with resilience in workers in the city of Jakarta. This study uses a correlational quantitative approach, with purposive sampling technique, where sampling is based on predetermined criteria. The data collection method uses a resilience scale, adaptation scale, and family support scale. The subjects in this study amounted to 360 people who worked in the city of Jakarta. The data analysis used is multiple regression analysis techniques. Based on the results of the study, it shows that there is a significant relationship between adaptation and family support with resilience in workers in the city of Jakarta.